2017
DOI: 10.22502/jlmc.v5i2.158
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter Pylori among Patients undergoing Gastrodudenoscopy in a Hospital in Western Nepal

Abstract: Introduction: Helicobacter pylori (H. pylori) related chronic gastritis is a major health problem worldwide, specially in the developing countries. The prevalence of H. pylori infection has been reported to vary between and even within countries. There are limited data on this infection in Western Nepal. Our objective was to study the prevalence of H. pylori infection and its association with presenting complains and upper gastrointestinal diseases. Methods: Medical records of patients undergoing gastrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…The majority of patients detected with H. pylori were from the age group of 41-60 years in the current study. The prevalence of H. pylori was, similarly higher in the same age group by Shakya et al 8 Our study did not show any significant difference in H. pylori prevalence among the gender. This was consistent with the previously published studies.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The majority of patients detected with H. pylori were from the age group of 41-60 years in the current study. The prevalence of H. pylori was, similarly higher in the same age group by Shakya et al 8 Our study did not show any significant difference in H. pylori prevalence among the gender. This was consistent with the previously published studies.…”
Section: Discussionsupporting
confidence: 61%
“…This was consistent with the previously published studies. [7][8][9] A study by Adlekha et al from India and KC et al from Nepal also showed no significant sex predilection for H. pylori infection. 10,11 The prevalence of H. pylori in patients with dyspepsia was 53.2% in the current study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[11] The prevalence is lower compared to a similar study from low socioeconomic country Ethiopia (81%). [12] H. pylori was positive in 67% of chronic gastritis patients, significantly lower than that described by Shakya RP (90%) 10 and much higher than the other Nepalese study by Shrestha UK (41%) [11] and Shrestha S (44%). [8] Diagnostic accuracy of stool antigen test in our study showed lower sensitivity and specificity compared with histopathological examination than described by Gisbert JP et al, which showed a mean sensitivity, specificity, positive predictive value and negative predictive value of 91%, 93%, 92% and 87%, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…However, this incidence is much higher than that in Lumbini region study from western Nepal. [10] Another study from Pokhara showed the overall prevalence of H. pylori to be only 29.4%. However, the prevalence was higher in symptomatic patients with gastritis, duodenitis, gastric and/or duodenal ulcers.…”
Section: Discussionmentioning
confidence: 99%